The causal impact of social connections on firms' outcomes - Marcus Eliason; Lena Hensvik; Francis Kramarz; Oskar Nordström Skans (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2017)
The paper studies how social connections affect firm-level hiring decisions and performance. We characterize the social connections of firms' employees using register data and for causal identification we use job displacements, which create directed positive shocks towards connected firms by increasing these firms' available supply of connected labor. We ascertain that our results are fully driven by these directed supply shocks. Our results show that firms appear to prefer to hire employed workers to whom they are connected over unconnected or unemployed workers. Employed and connected workers mostly go to high-productivity firms, whereas unemployed and unconnected workers tend to go to low-productivity firms. Strong connections - family, recent, durable, formed in small groups, between socially similar agents - matter the most. A displacement shock causes connected firms, in particular low-productive ones, to hire more of the connected workers, while leaving unconnected hires and separations essentially unaffected. Increases in the supply of connected labor, therefore, cause the creation of additional jobs at the firm level. By using these shocks, we can also show that hiring connected workers has a positive causal impact on firm performance. Our results are consistent with a stylized framework where connections reduce hiring frictions and where the firms' ability to hire connected workers is a function of these workers' outside options.
Keywords: J60; J30; J23; 330; Networks; job search; job displacement; job creation; Arbeitskräfte; Soziale Beziehungen; Soziales Netzwerk; Personalbeschaffung; Produktivität; Unternehmenserfolg; Personalabbau; Arbeitsuche; Schätzung; Schweden